Atrial arrhythmogenesis in obstructive sleep apnea: Therapeutic implications. (April 2016) - Linz, Dominik; Linz, Benedikt; Hohl, Mathias; Böhm, Michael
Summary: The prevalence of sleep disordered breathing like obstructive sleep apnea (OSA) among patients with atrial fibrillation (AF) is 40–50%. OSA reduces success rate of catheter based and pharmacological antiarrhythmic treatment. Additionally, efficient treatment of OSA by continuous positive airway pressure ventilation (CPAP), the first line therapy of OSA, has been shown to improve catheter ablation success rates in AF-patients. A systematic literature search using several databases was performed to review the pathophysiology of obstructive apneas in OSA potentially leading to the development of a substrate for AF and to explain potential mechanisms involved in the clinically observed atrial antiarrhythmic effect of effective CPAP therapy.